Informing the standardising of care for prolonged stay patients in the intensive care unit: A scoping review of quality improvement tools. (December 2022) - Allum, Laura; Apps, Chloe; Pattison, Natalie; Connolly, Bronwen; Rose, Louise
Abstract: Objectives: To inform design of quality improvement tools specific to patients with prolonged intensive care unit stay, we determined characteristics (format/content), development, implementation and outcomes of published multi-component quality improvement tools used in the intenisve care unit irrespective of length of stay. Research Methodology: Scoping review searching electronic databases, trial registries and grey literature (January 2000 to January 2022). Results: We screened 58, 378 citations, identifying 96 studies. All tools were designed for use commencing at intensive care unit admission except three tools implemented at 3, 5 or 14 days. We identified 32 studies of locally developed checklists, 28 goal setting/structured communication templates, 23 care bundles and 9 studies of mixed format tools. Most (43 %) tools were designed for use during rounds, fewer tools were designed for use throughout the ICU day (27 %) or stay (9 %). Most studies (55 %) reported process objectives i.e., improving communication, care standardisation, or rounding efficiency. Most common clinical processes quality improvement tools were used to standardise were sedation (62, 65 %), ventilation and weaning (55, 57 %) and analgesia management (58, 60 %). 44 studies reported the effect of the tool on patient outcomes. Of these, only two identified a negative effect; increased length of stay and increased days with pain and delirium. Conclusion: Although we identified numerous quality improvement tools for use in the intensive care unit, few were designed to specifically address actionable processes of care relevant to the unique needs of prolonged stay patients. Tools that address these needs are urgently required. Systematic review registration: The review protocol is registered on the Open Science Framework, https://osf.io/, DOI 10.17605/OSF.IO/Z8MRE